Spirituality under gentile captivity : David J. Bosch's missionary ecclesiology as a guide for spirituality - Nofziger, Dylon (Stellenbosch : Stellenbosch University, 2011)
Assignment (M. Div.)--University of Stellenbosch, 2006.